1975
DOI: 10.1139/p75-017
|View full text |Cite
|
Sign up to set email alerts
|

The (3He,d) Reaction on 69Ga

Abstract: Excited levels of 70Ge and proton holes in 69Ga have been investigated by means of the 69Ga (3He, d)70Ge reaction at an incident beam energy of 22.5 MeV. Angular distributions were measured and are compared with the prediction of the distorted-wave-Born-approximation (DWBA) theory in order to obtain the spectroscopic strengths of each level.The number of proton holes in 69Ga was obtained from the sum rule of the spectroscopic strengths. The vacancy probability UJ2 and the center of gravity energy EJ for the 2p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Several low-spin negative-parity states in 70 Ge were identified from the earliest studies of this nucleus using light-projectile reactions [5][6][7][8][9]11], heavy-ion reactions [12,13], and a more recent investigation of the β + decay of 70 As [10]. The lowest state with negative parity was first identified as the one at 2562 keV [8] with a likely spin of J = 3 [6].…”
Section: Negative-parity Bandsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several low-spin negative-parity states in 70 Ge were identified from the earliest studies of this nucleus using light-projectile reactions [5][6][7][8][9]11], heavy-ion reactions [12,13], and a more recent investigation of the β + decay of 70 As [10]. The lowest state with negative parity was first identified as the one at 2562 keV [8] with a likely spin of J = 3 [6].…”
Section: Negative-parity Bandsmentioning
confidence: 99%
“…Low-lying excited 0 + states are common among the even-even Ge isotopes, and 70 Ge is no exception. The 0 + 2 state in 70 Ge has been known since the earliest studies of this nucleus [5][6][7][8][9], and was later confirmed using fusion-evaporation reactions [13]. Higher-lying 2 + 3 and 4 + 3 states were found to decay to the 0 + 2 state through a sequence of γ rays with energy 941.10 and 901.95 keV following the β + decay of 70 As [10], providing confirmation of the 4 + 3 state observed in Refs.…”
Section: Excited 0 + 2 Bandmentioning
confidence: 99%
See 1 more Smart Citation